2015
DOI: 10.1111/clr.12554
|View full text |Cite
|
Sign up to set email alerts
|

Abutment height influences the effect of platform switching on peri‐implant marginal bone loss

Abstract: Greater mismatching does not minimize the MBL; abutment height, smoking habit, and bone substratum may play a role in the MBL over the short- and medium term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 39 publications
9
83
4
3
Order By: Relevance
“…15,16 In the present study, group 1 showed a low success rate and an increased mean MBL. 15,16 In the present study, group 1 showed a low success rate and an increased mean MBL.…”
Section: Resultscontrasting
confidence: 44%
See 1 more Smart Citation
“…15,16 In the present study, group 1 showed a low success rate and an increased mean MBL. 15,16 In the present study, group 1 showed a low success rate and an increased mean MBL.…”
Section: Resultscontrasting
confidence: 44%
“…Tarnow and colleagues 11 showed that a lateral component of the biologic width exists around implants. Galindo-Moreno and colleagues 15 and Vervaeke and colleagues 16 suggested that implants with longer abutments resulted in less MBL. [12][13][14] However, few studies have shown the relationship between the crown/abutment gap and MBL.…”
Section: Introductionmentioning
confidence: 99%
“…One other factor that has been shown to influence amount of marginal CBL around implants is height of the prosthetic abutment used. A recent study 40 has clearly shown that short abutments (<2 mm) demonstrate a more significant amount of CBL over time compared with longer abutments. Taking into consideration the fact that height of the abutment used is generally adapted to the site‐specific soft tissue thickness and apico‐coronal dimension, the biologic explanation for this finding could be provided by another study 41 that reported that the vertical soft tissue thickness plays a major part in the etiology of early CBL.…”
Section: Discussionmentioning
confidence: 97%
“…In their RCT, marginal bone preservation was significantly different between PS and platform‐matching connections only when mucosa was >4.22 mm. In this sense, Galindo‐Moreno et al recently reported that vertical mismatching, in relation with prosthetic abutment height, conditioned clinically by the keratinized mucosa width, is better than PS in the preservation of MBL 43 . Furthermore, results from a recent investigation of implants restored with PS have concluded that bone resorption is mainly related to BW re‐establishment rather than implant–abutment horizontal mismatching 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, results from a recent investigation of implants restored with PS have concluded that bone resorption is mainly related to BW re‐establishment rather than implant–abutment horizontal mismatching 18 . These studies shed light on the potential correlation of peri‐implant soft tissue thickness and MBL 18 , 42 , 43 . Interestingly, the influence of peri‐implant tissue thickness on MBL had never been systematically reviewed previously.…”
Section: Discussionmentioning
confidence: 99%